Diagnosis and possible interventions in designing livestock-based agroforestry systems in dryland tract of the Western zone of Tamil Nadu - A case study - Mynavathi, V.S.; Arunachalam, Ayyanadar (Indian Journal of Agroforestry, 2023)
A diagnostic survey for appraisal of existing livestock-based agroforestry systems and existing agroforestry practices in Western agroclimatic zones of Tamil Nadu was conducted during 2019-2020. Based on this study the major constraints in practicing livestock-based agroforestry systems were identified and possible interventions for integrating livestock were suggested. Farmers showed great interest for silvipasture systems followed by hortipasture and homestead-based agroforestry systems along with livestock components like dairy and goat rearing especially for satisfying the milk and meat requirements and vegetables for immediate cash and meeting out the household requirement. Some of the suitable fodder tree species for integration in designing livestock-based agroforestry systems identified are Leucaena leucocephala, Sesbania grandiflora, Sesbania sesban, Inga dulce, Gliricidia sepium, Albizia lebbeck and Acacia leucocephala. Integration of livestock component with agroforestry systems results in increased income to farmers due to enhanced crop production, reduced labour for rearing of livestock and improved soil fertility through application of manure from livestock rearing. Scientific management is required to improve the production of various components. Future research needs are also recommended for further improving the systems viability. It was also realized that when the desirable and viable components were integrated, the system would need to be evaluated for its functionality after a few years, and if necessary, it could be rediagnosed and redesigned to meet the desired goals.